Towards improved separation performance using porous FO membranes: The critical roles of membrane separation properties and draw solution - Qi, Saren (2015)
The use of porous membranes for forward osmosis (FO) applications has been recently reported in the literature. In the current study, a series of porous-FO membranes were fabricated to systematically study the role of membrane separation properties on the FO performance of porous membranes. In addition, two types of draw solutes, a polyelectrolye poly(sodium 4-styrene-sulfonate) (PSS) and a neutral linear polymer polyethylene glycols (PEGs), were evaluated as the draw solutes. The effect of draw solution properties (type of draw solutes, their molecular weight, and concentration) on the FO performance was investigated. Membrane post-treatment at higher annealing temperature was found to increase solute rejection and decrease water permeability. As a result, reverse solute diffusion (RDS) became less severe at higher annealing temperature. The FO water flux of the porous membranes was affected by RDS in addition to the water permeability of the porous FO membranes, both of which had a strong dependence on the annealing temperature. Compared to neutral PEG, the polyelectrolyte PSS was a much better choice for draw solutes with higher FO water flux and lower RDS. The better performance of PSS can be attributed to its higher rejection by the porous FO membranes and its high osmotic pressure compared to PEG at same weight concentration. Implications for the design of porous FO membranes and draw solution are discussed.